2018
DOI: 10.1126/science.aan8782
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of adatom-promoted graphene growth on nickel

Abstract: Single adatoms are expected to participate in many processes occurring at solid surfaces, such as the growth of graphene on metals. We demonstrate, both experimentally and theoretically, the catalytic role played by single metal adatoms during the technologically relevant process of graphene growth on nickel (Ni). The catalytic action of individual Ni atoms at the edges of a growing graphene flake was directly captured by scanning tunneling microscopy imaging at the millisecond time scale, while force field mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
110
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(117 citation statements)
references
References 30 publications
(31 reference statements)
5
110
0
2
Order By: Relevance
“…The EDS test (Figure h–j; Figure S2, Supporting Information) further confirmed the presence of Ni element, and the atomic percentages of C, O, and Ni were 93.91: 5.92: 0.17. More importantly, it can be seen from Figure j that more Ni elements are distributed at the edge curl of the 3D ECG, consistent with the migration of Ni in the graphene growth speculated by the synthetic method …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The EDS test (Figure h–j; Figure S2, Supporting Information) further confirmed the presence of Ni element, and the atomic percentages of C, O, and Ni were 93.91: 5.92: 0.17. More importantly, it can be seen from Figure j that more Ni elements are distributed at the edge curl of the 3D ECG, consistent with the migration of Ni in the graphene growth speculated by the synthetic method …”
Section: Resultssupporting
confidence: 78%
“…This process is demonstrated by Process ④ and Process ⑤ in Figure . As the carbon is continuously dissolved‐precipitated on the Ni particles, the graphene net continues to grow, and the newly formed graphene pushes the Ni particles forward . The migration of Ni during this process is similar to the movement of Ni particles to catalyze the growth of carbon nanotubes .…”
Section: Resultsmentioning
confidence: 99%
“…[141] With a matched lattice (246 vs 249 pm) as well, graphene can readily grow on Ni(111) as a desired substrate via physical vapor deposition. [143] As shown in Figure 10, the catalytic action of individual Ni atoms at the edges of a growing graphene flake was directly captured by scanning tunneling microscopy with a time resolution down to milliseconds, and further rationalized by force field molecular dynamics and DFT calculations. [143] As shown in Figure 10, the catalytic action of individual Ni atoms at the edges of a growing graphene flake was directly captured by scanning tunneling microscopy with a time resolution down to milliseconds, and further rationalized by force field molecular dynamics and DFT calculations.…”
Section: Nickel Nanostructuresmentioning
confidence: 99%
“…Graphene growth along Zigzag (z) and Klein (k) edges on Ni(111). Reproduced with permission [143]. b,c) Highspeed scanning tunneling microscopy acquired in quasi-constant height mode at the z edge b) and the k edge c).…”
mentioning
confidence: 99%
“…The diversity of the graphene samples and methods of the production, in turn, drives the development of new characterization techniques. For example, FAST‐STM achieves an imaging rate at the millisecond time scale, enabling real‐time observation of the catalytic activity of single metal atom and the atomic growth of graphene edge. More recently, Patera et al demonstrated a single electron alternate‐charging STM based on synchronizing the voltage pulses and the oscillation of a conductive atomic force microscope tip.…”
Section: Resultsmentioning
confidence: 99%